Pengaruh Promosi Online dan Online Customer Review Terhadap Keputusan Pembelian pada Produk Scarlett Whitening di Shopee (Studi pada Pengguna Produk Scarlett Whitening di Kota Makassar) - Asisa Nurfadila Rasyid; Burhanuddin Burhanuddin; Muhammad Ilham Wardhana Haeruddin; Chalid Imran Musa; Nurul Fadilah Aswar (Journal of Management and Creative Business, 2025)
This study aims to determine the Influence of Online Promotion and Online Customer Review on Purchase Decisions for Scarlett Whitening Products. This study is a quantitative study with a non-probability sampling technique. The sample used in this study was 100 residents of Makassar. Data collection was carried out using the library study method and survey using a questionnaire. Based on the results of the study, the results of the f test showed a significance value of 0.000 <0.05, which means that the independent variables (Online promotion and Online customer review) simultaneously have a positive and significant influence on the dependent variable (purchase decision). While the t test obtained a significance value of the Online promotion variable of 0.005 <0.05, which means that the variable (X1) Online promotion partially has a positive and significant influence on the variable (Y) purchasing decision. And the Online customer review variable has a significance value of 0.000 <0.05, which means that the variable X2 (Online customer review) partially has a positive and significant influence on the variable (Y) purchasing decision.